Effect of the catalyst MCM-41 on the kinetic of the thermal decomposition of poly(ethylene terephthalate) - Araujo, Sulene A.; Araujo, Antonio S.; Fernandes, Nedja S.; Fernandes, Valter J.; Ionashiro, Massao [UNESP] (Springer, 2010)
The aim of this work is to determine the activation energy for the thermal decomposition of poly (ethylene terephthalate)-PET, in the presence of a MCM-41 mesoporous catalyst. This material was synthesized by the hydrothermal method, using cetyltrimethylammonium as template. The PET sample has been submitted to thermal degradation alone and in presence of MCM-41 catalyst at a concentration of 25% in mass (MCM-41/PET). The degradation process was evaluated by thermogravimetry, at temperature range from 350 to 500 degrees C, under nitrogen atmosphere, with heating rates of 5, 10 and 25 degrees C min(-1). From TG, the activation energy, determined using the Flynn-Wall kinetic method, decreased from 231 kJ mol(-1), for the pure polymer (PET), to 195 kJ mol(-1), in the presence of the material (MCM-41/PET), showing the catalyst efficiency for the polymer decomposition process.
Keywords: Poly(ethylene terephthalate); MCM-41; Flynn-Wall kinetic model; Thermogravimetry